Why does the yield curve predict GDP growth? The role of banks - Camelia Minoiu; Andrés Schneider; Min Wei (Federal Reserve Bank of Atlanta, 2023)
We provide evidence on the effect of the slope of the yield curve on economic activity through bank lending. Using detailed data on banks' lending activities coupled with term premium shocks identified using high-frequency event study or instrumental variables, we show that a steeper yield curve associated with higher term premiums (rather than higher expected short rates) boosts bank profits and the supply of bank loans. Intuitively, a higher term premium represents greater expected profits on maturity transformation, which is at the core of banks' business model, and therefore incentivizes bank lending. This effect is stronger for ex-ante more leveraged banks. We rationalize our findings in a portfolio model for banks.
Keywords: E44; E52; E58; 330; predictive power of the yield curve; term spread; term premium; bank lending; bank probability; event study; instrumental variable